Psoriatic arthritis is associated with adverse body composition predictive of greater coronary heart disease and type 2 diabetes propensity – a cross-sectional study. (4th November 2020) - Ferguson, Lyn D; Linge, Jennifer; Dahlqvist Leinhard, Olof; Woodward, Rosemary; Hall Barrientos, Pauline; Roditi, Giles; Radjenovic, Aleksandra; McInnes, Iain B; Siebert, Stefan; Sattar, Naveed
Abstract: Objectives: To compare body composition in PsA with metabolic disease free (MDF) controls and type 2 diabetes and assess body-composition predicted propensity for cardiometabolic disease. Methods: Detailed MRI body composition profiles of 26 PsA participants from the IMAPA study were compared with 130 age, sex and BMI-matched MDF controls and 454 individuals with type 2 diabetes from UK Biobank. The body-composition predicted propensity for coronary heart disease (CHD) and type 2 diabetes was compared between PsA and matched MDF controls. Results: PsA participants had a significantly greater visceral adipose tissue (VAT) volume [mean 5.89 l (s .d . 2.10 l)] compared with matched-MDF controls [mean 4.34 l (s .d . 1.83 l)] ( P <0.001) and liver fat percentage [median 8.88% (interquartile range 4.42–13.18%)] compared with MDF controls [3.29% (1.98–7.25%)] ( P <0.001). These differences remained significant after adjustment for age, sex and BMI. There were no statistically significant differences in VAT, liver fat or muscle fat infiltration (MFI) between PsA and type 2 diabetes. PsA participants had a lower thigh muscle volume than MDF controls and those with type 2 diabetes. Body composition-predicted propensity for CHD and type 2 diabetes was 1.27 and 1.83 times higher, respectively, for PsA compared with matched-MDF controls. Conclusion: Individuals with PsA have an adverse body composition phenotype with greater visceral and ectopic liver fat and lower thigh muscle volume than matched MDF controls. Body fat distribution in PsA is more in keeping with the pattern observed in type 2 diabetes and is associated with greater propensity to cardiometabolic disease. These data support the need for greater emphasis on weight loss in PsA management to lessen CHD and type 2 diabetes risk.